2015
DOI: 10.5195/cajgh.2015.134
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension and associated factors in Jalalabad City, Nangarhar Province, Afghanistan

Abstract: Background:Hypertension affects an estimated one billion people, worldwide. It is a public health challenge characterized by increased morbidity, mortality, as well as cost to the community and health systems. The goal of this study is to determine the prevalence of hypertension and characterize associated risk factors in an urban setting in Afghanistan.Methods:A cross-sectional study of adults aged 25-65 years was conducted in Jalalabad city from May to June 2013 using the World Health Organization STEPwise a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 12 publications
5
24
2
Order By: Relevance
“…This study revealed that the prevalence of hypertension in the urban setting of Kandahar in Afghanistan is 32.3%, indicating that almost one third of the adult population of this city is suffering from this public health problem. These findings are supported by being comparable to other findings of national (13,14) and international studies (23,24). It further reveals that the country has entered into an epidemic of noncommunicable diseases such as hypertension, while in the last decade the country has focused on infectious diseases, nutrition, and maternal health (25,26).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This study revealed that the prevalence of hypertension in the urban setting of Kandahar in Afghanistan is 32.3%, indicating that almost one third of the adult population of this city is suffering from this public health problem. These findings are supported by being comparable to other findings of national (13,14) and international studies (23,24). It further reveals that the country has entered into an epidemic of noncommunicable diseases such as hypertension, while in the last decade the country has focused on infectious diseases, nutrition, and maternal health (25,26).…”
Section: Discussionsupporting
confidence: 81%
“…In Afghanistan, there is lack of information on NCDs including hypertension due to priority given to communicable diseases. Prevalence of hypertension in Kabul and Jalalabad in adult population is found to be 46.2% and 28.4%, respectively (13,14). Two neighboring countries of Afghanistan, Iran and Pakistan, have estimated the prevalence of hypertension to be 22.1% and 25.3%, respectively (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…15 However, the prevalence of other studies conducted in India 29.3% 16 , in the northwestern tip of Penang Island, Malaysia 29.8%, 17 in middle Anatolian city 24.2% 18 and in Jalalabad City, Nangarhar Province, Afghanistan 28.4% 19 were lower than that of current study.…”
Section: Discussioncontrasting
confidence: 63%
“…Another study from Afghanistan showed that hypertension was significantly associated with obesity, and physical activity. 19 Hypertension was also significant associated with BMI and physical activity at work in the study of Malekzadeh et. al.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation